2005
DOI: 10.1242/dev.02038
|View full text |Cite
|
Sign up to set email alerts
|

Slit-mediated repulsion is a key regulator of motor axon pathfinding in the hindbrain

Abstract: The floor plate is known to be a source of repellent signals for cranial motor axons, preventing them from crossing the midline of the hindbrain. However, it is unknown which molecules mediate this effect in vivo. We show that Slit and Robo proteins are candidate motor axon guidance molecules, as Robo proteins are expressed by cranial motoneurons, and Slit proteins are expressed by the tissues that delimit motor axon trajectories, i.e. the floor plate and the rhombic lip. We present in vitro evidence showing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
108
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 76 publications
(129 citation statements)
references
References 55 publications
17
108
4
Order By: Relevance
“…The neuroepithelial labeling in the brain and spinal cord is consistent with previous expression studies of Robo1 mRNA (Connor and Key, 2002;Hammond et al, 2005;Sundaresan et al, 1998). However, two independent Robo1 antibodies, neither isoform-specific, have been used to label spinal cord sections, with labeling in post-crossing commissural axons and not in neuroepithelium (Long et al, 2004;Sundaresan et al, 2004).…”
Section: Dutt1 Has Broad Expression In Neuronal and Non-neuronal Tissuesupporting
confidence: 86%
See 2 more Smart Citations
“…The neuroepithelial labeling in the brain and spinal cord is consistent with previous expression studies of Robo1 mRNA (Connor and Key, 2002;Hammond et al, 2005;Sundaresan et al, 1998). However, two independent Robo1 antibodies, neither isoform-specific, have been used to label spinal cord sections, with labeling in post-crossing commissural axons and not in neuroepithelium (Long et al, 2004;Sundaresan et al, 2004).…”
Section: Dutt1 Has Broad Expression In Neuronal and Non-neuronal Tissuesupporting
confidence: 86%
“…The best studied commissural neurons arise in dorsal spinal cord near the roof plate and project their axons ventrally, crossing the midline under Robo guidance (Long, et al, 2004). In dorsal spinal cord neurons, Dutt1 expression was much more extensive than Robo1, indicating that the Dutt1 isoform is the predominant isoform in commissural axons.The neuroepithelial labeling in the brain and spinal cord is consistent with previous expression studies of Robo1 mRNA (Connor and Key, 2002;Hammond et al, 2005;Sundaresan et al, 1998). However, two independent Robo1 antibodies, neither isoform-specific, have been used to label spinal cord sections, with labeling in post-crossing commissural axons and not in neuroepithelium (Long et al, 2004;Sundaresan et al, 2004).…”
supporting
confidence: 86%
See 1 more Smart Citation
“…Chicken embryos were obtained (26) and then used for immunostaining, in situ hybridization, immunohistochemistry (17), or in ovo electroporation as previously described (27). All experiments were approved by the ethical review committee of King's College London.…”
Section: Methodsmentioning
confidence: 99%
“…Slits are expressed in the floor plate, the rhombic lip and in several cranial motor nuclei, such as the facial nucleus (Geisen et al, 2008;Gilthorpe et al, 2002;Hammond et al, 2005). In vitro assays had previously shown that Slits can repel migrating precerebellar neurons (Causeret et al, 2002; Causeret et al, 2004;Gilthorpe et al, 2002).…”
Section: Repulsion and Cell Polaritymentioning
confidence: 99%